2017
DOI: 10.1101/188102
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolomics reveals that dietary xenoestrogens alter cellular metabolism induced by palbociclib/letrozole combination cancer therapy

Abstract: HighlightsSynergism of combined palbociclib/letrozole chemotherapy was examined by global metabolomicsCombination therapy led to more pronounced effects on the MCF-7 metabolome than single agentsDietary phyto- and mycoestrogens significantly affected the metabolic and anti-oncogenic response of the drugsImplications of these bio-active chemicals on therapeutic success in breast cancer patients appear plausibleIn BriefWarth et al. used innovative global metabolomics and pathway prediction technology to describe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Others continue to emerge, whereby, for example, a recent untargeted mass spectrometry-based metabolomics study identified a form of 2-HG, 2-hydroxyglutarate-lactone, that exists in human cells for which the regulation and putative function apart from 2-HG is unknown (53). Although we do not summarize the vast number of diet-derived bioactive metabolites that also continue to emerge such as phytoestrogens (54). Furthermore, some endogenous metabolites act as riboswitches to influence gene expression (55).…”
Section: Othersmentioning
confidence: 95%
“…Others continue to emerge, whereby, for example, a recent untargeted mass spectrometry-based metabolomics study identified a form of 2-HG, 2-hydroxyglutarate-lactone, that exists in human cells for which the regulation and putative function apart from 2-HG is unknown (53). Although we do not summarize the vast number of diet-derived bioactive metabolites that also continue to emerge such as phytoestrogens (54). Furthermore, some endogenous metabolites act as riboswitches to influence gene expression (55).…”
Section: Othersmentioning
confidence: 95%
“…Whether they are free or commercial tools, the processing is mainly the same, although it may differ in how the steps are carried out, some of them working with in-house made algorithms. In the literature reviewed, the most employed tools were open-source software as XCMS (R package or Online) [17,18,75,76], MZmine [16,77] and MetAlign [78]; and commercial software as Mass Profiler Pro (Agilent Technologies Inc.) [79,80], Progenesis QI (Non Linear Dynamics, Waters) [15,25,72], MarkerLynx (Waters) [81,82], SIEVE [49,85,86].…”
Section: Data Processingmentioning
confidence: 99%
“…The controlled trial study of fish oil supplementation during pregnancy, ended in the detection of several altered metabolic pathways significantly associated with a reduced risk of asthma by age 5 [124]. Likewise, the effects of diets supplements were assessed, as selenium impact on metabolic disorders [93] or the use of xenoestrogens in combination with cancer therapy [76].…”
Section: Food and Health Effectsmentioning
confidence: 99%